PENGARUH PRODUK, PELAYANAN DAN AGAMA TERHADAP LAYANAN GADAI EMAS BANK SYARIAH INDONESIA KCP TOMONI - Nur Hishaly GA (Journal of Institution and Sharia Finance, 2023)
This research discusses the influence of products, services and religion on the gold pawning services of Bank Syariah Indonesia KCP Tomoni. This research aims to partially describe the influence of services, products and religion on the gold pawning services of Bank Syariah Indonesia KCP Tomoni; and also describe the influence of services, products and religion simultaneously on the gold pawning services of Bank Syariah Indonesia KCP Tomoni. The type of research is quantitative research. The population is customers using the gold pawning service of Bank Syariah Indonesia KCP Tomoni. Meanwhile, the sampling technique in this research is Quota Sampling with a sample of 77 customers using the Slovin formula. The data collection technique in this research is by distributing questionnaires to respondents. The results of this research show that: 1) The service variable has a positive and significant effect on the gold pawning service of Bank Syariah Indonesia KCP Tomoni. 2) The product variable has a positive and significant effect on the gold pawning service of Bank Syariah Indonesia KCP Tomoni. 3) The religious variable has a positive and significant effect on the gold pawning services of Bank Syariah Indonesia KCP Tomoni. 4) The variables of service, product and religion simultaneously have a positive and significant effect on the gold pawning service of Bank Syariah Indonesia KCP Tomoni.